LIFEBIO: LIFE STORIES OF OLDER ADULTS TO REDUCE LONELINESS AND IMPROVE SOCIAL CONNECTEDNESS. (11th November 2018) - Keown, K; Tkatch, R; Martin, D; Duffy, M; Wu, L; Schaeffer, J; Wicker, E
Abstract: The writing of an autobiography can be considered a form of life-review therapy, which has been associated with a number of positive health outcomes including improved depression and loneliness. This LifeBio program is designed as a group intervention to engage participants and capture their life stories in order to positively impact wellness through reminiscence. This program was adapted telephonically for Aging Strong 2020. Data collection for Cohort 1 is complete. Thirty participants completed the 6-week program. Pre- and post-surveys were mailed to the participants along with a journal to use with the program. Outcome measures include loneliness, social connectedness, and all other Aging Strong 2020 measures (e.g. optimism, purpose in life, resilience). Post survey results found that for those who were moderately to severely lonely at the baseline, the program reduced loneliness and improved social support (p<.05). Life story reminiscence has the potential to impact the well-being of older adults.